Analysis of the Number of Intercity Passengers Via Trans Java Island for the Period 2023-2024 at the DAMRI Bus Terminal - Prasetyo; Aprilia Dwi Aisyah; Lasron Saputra Lumbanraja; Rovia Ramadhani; Erni Putri Setia Zendrato; Silvi yani; Ellin Marlina; Rafli Pahlevi; Miftakul Huda (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study examines ticket sales trends during the 2024 Lebaran Transportation period at DAMRI Bus Terminals, focusing on various intercity routes. DAMRI, a leading public transportation company in Indonesia, prioritizes performance, quality, and passenger safety in its services. Data analysis reveals significant ticket sales across routes such as Surabaya-Malang, Lampung, and Pontianak, indicating passenger preferences during peak travel seasons. The results of this study provide valuable insights to optimize intercity transportation services and meet passenger demand effectively